Building Malaysian green economy model for socio-economic development - Negin Vaghefi,; Chamhuri Siwar,; Sarah Aziz Abdul Ghani Aziz, (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2017)
In the face of economic development, the gap between industrialized and developing countries are still large, and problems associated with the environment have crucially increased. Resource prices are rising and competition for scarce resources has also increased. This is a serious challenge especially for countries that are experiencing industrialization and rapid economy growth like Malaysia. In fact, the environmental, social and economic dimensions are reflected in the green economy concept. Malaysia’s national green economy framework attempts to strengthen the economy through incentives, tax, pricing, regulating and investments. However, it is mostly focused on industries located in urban areas and the social dimension is not clearly made in terms of program and policy tools. This paper introduces a conceptual framework to create Malaysian green economy model for socio-economic development and indicates the endogenous links within and across the economic, social and environmental sectors. It defines pathway to sustainable development which is about government intervention that helps the economy to determine the technological changes. This study is therefore an overview of the initiatives and opportunities for green economy implementation in Malaysia.